Development of Taman Ghanjaran Tourist Village from the Perspective of Dynamic Governance in Ketapanrame Village, Trawas District, Mojokerto Regency - Sri Roekminiati; Sapto Pramono; Ika Devi Pramudiana; Rayhan Al Ghavara Heda; Firdiansyah Arief Arianto (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to describe and analyze the development of the Taman Ghanjaran tourist village in Ketapanrame, managed by BUMDesa "Mutiara Welirang," to enhance the Taman Ghanjaran tourist village. The type of research is qualitative descriptive. This study focuses on the development of tourist villages based on dynamic governance, particularly on dynamic capabilities including 1) thinking ahead; 2) thinking again; and 3) thinking across. The results indicate that the capability of thinking ahead requires stakeholders to leverage existing potential. The decision by the Village Head, BPD, and the community to utilize unproductive absorption land for a park was sound. This is reinforced by establishing a clear vision, mission, and strategies for the future and collaborating with various parties to address future challenges continuously. The capacity for thinking again suggests that some policies need to be revised to address the declining visitor numbers at Taman Ghanjaran. BUMDes, under the tourism unit, should develop community investment programs in Ketapanrame through KUB (Business Groups). Digital promotion is now a necessity that cannot be overlooked. The capacity for thinking across has already been implemented in the development of Taman Ghanjaran. Although in 2023 it received the Indonesian Village Tourism Award (ADWI), efforts should not stop; continuous improvement and innovation in all areas are necessary